7-AMINO-2-HEPTENOATE UND IHRE VERWENDUNG IN DER HERSTELLUNG VON METHYLPHENIDAT - FOX, MARTIN, EDWARD; PAUL, JANE, MARIE (2002)
PCT No. PCT/GB97/00811 Sec. 371 Date Sep. 25, 1998 Sec. 102(e) Date Sep. 25, 1998 PCT Filed Mar. 21, 1997 PCT Pub. No. WO97/35836 PCT Pub. Date Oct. 2, 1997The subject invention pertains to compounds of the formula Y1Y2N-(CH2)4-CH=C(Ph)-X wherein Y1 and Y2 are independently H or a removable blocking group, or Y1 and Y2 together are a removable divalent blocking group; and X is COOCH3 or a group convertible thereto. Such a compound may be cyclised, by Michael addition, to give methylphenidate, if necessary after removing blocking group(s) and converting X to COOCH3. The subject invention also pertains to methods for preparing compounds of the invention.